2012
DOI: 10.1242/jcs.096818
|View full text |Cite
|
Sign up to set email alerts
|

TPPP acts downstream of RhoA-ROCK-LIMK2 to regulate astral microtubule organization and spindle orientation

Abstract: SummaryThe actin cytoskeleton in eukaryotic cells undergoes drastic rearrangement during mitosis. The changes to the actin cytoskeleton are most obvious in the adherent cells, where the actin stress fibres are disassembled, and the cortical actin network becomes more prominent with concomitant increase in cell rigidity as cells round up and enter mitosis. Although the regulatory connections between the actin cytoskeleton and the early mitotic events are apparent, the mechanisms that govern these links are not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 35 publications
6
45
1
Order By: Relevance
“…We show that TPPP1 phosphorylation by ROCK has no effect on its tubulin polymerizing activity, suggesting that the conformational changes induced by ROCK phosphorylation do not alter its interaction with MTs. We also clearly demonstrate that ROCK1, and not the LIMKs, is responsible for TPPP1 phosphorylation, as claimed previously (24,26). As the ROCKs strongly interact and copurify with the LIMKs, the previously published findings are likely to reflect TPPP1 phosphorylation by ROCK but not by LIMKs, as demonstrated in this study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We show that TPPP1 phosphorylation by ROCK has no effect on its tubulin polymerizing activity, suggesting that the conformational changes induced by ROCK phosphorylation do not alter its interaction with MTs. We also clearly demonstrate that ROCK1, and not the LIMKs, is responsible for TPPP1 phosphorylation, as claimed previously (24,26). As the ROCKs strongly interact and copurify with the LIMKs, the previously published findings are likely to reflect TPPP1 phosphorylation by ROCK but not by LIMKs, as demonstrated in this study.…”
Section: Discussionsupporting
confidence: 90%
“…Lysates were analyzed for LIMK1, LIMK2, GAPDH (loading control), and p-cofilin as a measure of LIMK activity. 22j (30), as it was suggested that the LIMKs phosphorylate TPPP1 (24,26)). We showed that although inhibition of LIMK activity decreased the phosphorylation of its substrate cofilin (Fig.…”
Section: Rock Signaling Modulates Tubulin Acetylation-inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that the LIM-kinase (LIMK) family members LIMK1 and LIMK2 interact with the microtubule regulatory protein Tubulin Polymerization Promoting Protein 1 (TPPP1) [6] [8] [17]. Contrary to the initial data indicating that TPPP1 is an in vitro LIMK substrate [6] [17], we established that the LIMKs do not phosphorylate TPPP1 and that it is a substrate of ROCK in cells [9].…”
Section: Limk1/tppp1/hdac6 Form a Trimeric Complexcontrasting
confidence: 56%
“…However, by focusing on how LIM kinase activity influences processes involved in cell motility and invasion, reports of negative roles of LIM kinase on functions such as cell cycle regulation may have been overlooked. Elevated LIMK2 levels following DNA damage were found to promote G 2 /M arrest via cofilin,46 which is consistent with a proposed role for LIMK2 during mitosis in regulating microtubule organisation and spindle orientation 47 48. Given that expression of the LIMK2a and LIMK2b variants has also been reported to be reduced in thyroid cancers,46 it will be important to re-consider how LIMK2 contributes to specific cancers rather than attempting to construct a unified theory.…”
Section: Discussionmentioning
confidence: 59%